The Exact and Near Optimal Solution of the Competitive Uncapacitated Location Problem - Lubos Buzna (Communications - Scientific letters of the University of Zilina, 2005)
This paper is dedicated to the recent unprecedented boom of new supermarkets and hypermarkets in middle Europe. The motivation is to provide for the newcomers the tool for decision support, and to help answer the questions: “Is still economically advantageous to build new shopping malls and where to locate them?” We introduce the four versions of data correcting algorithm and three heuristics: simple exchange heuristic, exchange heuristics enhanced by simulated annealing metaheuristic, and genetic algorithm. All these methods were examined at the benchmarks of practical nature. This research showed the data correcting method as useable for practical instances of this problem. There were also identified interesting dependencies between the computational time and the number of competitors.